Power optimized SRAM cell with high radiation hardened for aerospace applications. (September 2020) - Prasad, Govind; Mandi, Bipin Chandra; Ali, Maifuz
Abstract: The SRAM cells suffer from soft errors under high radiation environment like aerospace and satellite applications. Few radiations hardened based popular cells are 12T Dice and 12T We-Quatro. But these cells required more area and power consumption. To address these problems a 10T SRAM cell is designed, which gives perfect balance among all the parameters with higher delay. Hence, it is the most suggestible cell under high radiation environment. However, the 10T SRAM cell for high frequency under process variations gives a large number of write failure, which impeding the application of 10T SRAM cell. In this paper, a new SRAM cell has been proposed, which provides less power, more stability, less area, and very high soft error resilience. The proposed cell provides 17.48%, 5.26% less static power loss compared to We-Quatro and Dice, respectively. The total power loss of the proposed cell is reduced by 39.26%, 9.56% compared to We-Quatro and Dice cell respectively. The hold stability is increased by 45%, 81.59% compared to We-Quatro and Dice cell respectively. Also, the proposed cell gives moderate area overhead, comparable write speed, and perfect balance among all the parameters. The proposed cell is also verified using Monte Carlo (M.C) simulation in 45 nm CMOS technology.